Optimalisasi Pendapatan Rumah Tangga: Pemanfaatan Lahan Pekarangan Produktif Melalui Budidaya Buah Naga - Siti Nuke Nurfatimah; Lia Dwi Martika; Winda Oktaviani; Saputra, Yoga Dwi; Dwiyanti, Sepira (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The demand for horticultural products, particularly the Golden Isis variety of dragon fruit, continues to increase along with population growth and expanding market needs. However, limited land availability, low community skills in cultivation, and disturbances from wild animals have hindered the Mitra Makmur farmer group in Sadamantra Village from meeting this demand. This community service program aims to enhance the community’s capacity in yard-based dragon fruit cultivation as an alternative source of household income, while also strengthening business management and financial administration within the farmer group. The implementation method consisted of five main stages: socialization, training (cultivation, business planning, and financial management), application of simple technologies (lightweight steel poles and solar-powered lamps), mentoring and evaluation, and designing a program sustainability strategy.The results of the program showed a significant improvement in knowledge of cultivation techniques, business plan development skills, and financial literacy. In addition, 25 households successfully realized dragon fruit cultivation in their yards by installing lightweight steel poles as supporting structures. The program also encouraged positive social changes, including increased awareness of productive yard utilization, active involvement of farmer group members in business management, and the emergence of a collaborative culture in collective marketing systems. Thus, this program not only improved the community’s technical skills but also strengthened local economic resilience and opened opportunities for sustainable horticultural business development.